Intense Pulsed Light Therapy with Optimal Pulse Technology as an Adjunct Therapy for Moderate to Severe Blepharitis-Associated Keratoconjunctivitis - Fang Ruan; Yunxiao Zang; Ruti Sella; Hongshuang Lu; Shang Li; Ke Yang; Tao Jin; Natalie A. Afshari; Zhiqiang Pan; Ying Jie (Journal of Ophthalmology)
Purpose. To evaluate the intense pulsed light (IPL) therapy with optimal pulse technology (OPT, M22™, Lumenis, USA) as an adjunct therapy for the prevention of recurrences in moderate to severe blepharokeratoconjunctivitis (BKC). Methods. This open-label nonrandomized clinical trial evaluated 33 patients diagnosed with BKC. Twenty-one patients received four bilateral OPT therapy sessions with Meibomian gland expression (MGX) (treatment group), and 11 patients received MGX alone (controls). This trial was initiated after a four-week pharmacotherapy for BKC in both groups and was scheduled at four-week intervals. Efficacy outcome measures included meibum quality, Meibomian gland (MG) secretion function, eyelid margin signs, corneal fluorescein staining (CFS) score, noninvasive keratography breakup time (NIKBUT), ocular surface disease index (OSDI) score, Schirmer I test (SIT), classification of tear film lipid layer (TFLL), and Meibomian gland dropout (MGDR). Safety outcome measures included visual acuity, intraocular pressure, eye structure damage, and facial skin appearance at each visit. Results. Quality of meibum, MG expressibility, eyelid margin signs, and OSDI score showed a statistically significant greater improvement in the treatment group after one to three treatment sessions, compared to controls (p<0.05). While these improved in both groups in comparison to baseline, the NIKBUT and upper and lower eyelid MGDRs significantly improved only in the treatment group (p<0.05). No adverse events occurred in both groups. No BKC recurrences were noted in the treatment group. Conclusions. IPL is a safe and effective adjuvant treatment for BKC and possibly more effective in reducing eyelid margin inflammation and prevents recurrences than MGX alone. This trial is registered with ChiCTR-ONN-17013864.